2018
DOI: 10.1515/ijnes-2017-0039
|View full text |Cite
|
Sign up to set email alerts
|

Student Preparation for Nursing Leadership: Lessons from an Undergraduate Programs Review

Abstract: Facilitating student achievement of nationally recognized entry-level-competencies in nursing leadership is a critical step in building capacity to promote patient safety, quality of care, and healthy work environments. Data for this substudy were drawn from a larger multi-phased, multi-method, cross-sectional, descriptive study conducted to inform comprehensive undergraduate curricular revision. The research question for this substudy was: what are the perceptions about undergraduate program preparation for n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…Parmenter found that not all placements provided students with leadership learning opportunities and supervisors did not routinely support students in applying leadership concepts in practice. However, the students found the simulated experiences to be beneficial, a finding reinforced by Ross et al (). Support for leadership learning from practice supervisors was highlighted in other studies: Pepin et al () reports the significance of good clinical role models; sadly, Francis‐Shama () described students' descriptions of a ‘fierce’ culture in clinical practice with ‘toxic’ mentors and destructive leadership styles.…”
Section: Methodsmentioning
confidence: 75%
See 3 more Smart Citations
“…Parmenter found that not all placements provided students with leadership learning opportunities and supervisors did not routinely support students in applying leadership concepts in practice. However, the students found the simulated experiences to be beneficial, a finding reinforced by Ross et al (). Support for leadership learning from practice supervisors was highlighted in other studies: Pepin et al () reports the significance of good clinical role models; sadly, Francis‐Shama () described students' descriptions of a ‘fierce’ culture in clinical practice with ‘toxic’ mentors and destructive leadership styles.…”
Section: Methodsmentioning
confidence: 75%
“…Educators might struggle with their responsibility to support students in practice (O'Driscoll, Allan, & Smith, ) perhaps due to heavy workloads or skills deficits. Some nursing students were exposed to negative cultures during clinical placements, ones which included bullying and horizontal violence (Ross et al, ). Regrettably, Nicotera and Clinkscales () suggest that bullying is viewed as an acceptable aspect of nursing practice and students often report being ignored and humiliated by registered colleagues (Rosser et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enfermeiros que desempenham papel de líderes, em geral, não receberam educação formal sobre liderança (1) . Aqueles com conhecimentos clínicos e eficácia comprovada no processo de cuidar são promovidos e vão adquirindo habilidades para a liderança, sem apoio institucional.…”
Section: Introductionunclassified